Analysis Of the Economic Functioning of Public Transport in Krakow - Maciej GLINIAK; Arkadiusz BIESZCZAD; Beata CHUDY; Kamil LITEWKA (Communications of International Proceedings, 2023)
The aim of this work is to analyze the functioning of public transport in the economic aspect, which will be carried out on the example of the city of Krakow. At the beginning of the work, public transport was described as the basis for sustainable city development. The next part was devoted to the economic dimension of the functioning of public transport. At the end of the work, a general characteristic of public transport in the economic aspect in Krakow was made, and its effectiveness was assessed. For this purpose, three indicators were calculated, such as return of sales, return of equality, return from assets. Appropriate public transport is extremely important for the sustainable development of the city. It is a key element in ensuring mobility, comfort and a good standard of living for the inhabitants of cities and neighboring agglomerations. The economic aspect of public transport affects the availability, quality and comfort of public transport. Effective management of public transport brings positive financial results, which translates into the availability and quality of public transport. As a result of the analysis, problems of MPK Kraków were identified, affecting the economic indicators they achieved, and examples of actions that could improve the company's situation were presented.
Keywords: public transport; analysis; economy